Recent Advances in Visible-Light Photoredox Catalysis for the Thiol-Ene/Yne Reactions - Qian Xiao; Qing-Xiao Tong; Jian-Ji Zhong (Molecules, 2022)
Visible-light photoredox catalysis has been established as a popular and powerful tool for organic transformations owing to its inherent characterization of environmental friendliness and sustainability in the past decades. The thiol-ene/yne reactions, the direct hydrothiolation of alkenes/alkynes with thiols, represents one of the most efficient and atom-economic approaches for the carbon-sulfur bonds construction. In traditional methodologies, harsh conditions such as stoichiometric reagents or a specialized UV photo-apparatus were necessary suffering from various disadvantages. In particular, visible-light photoredox catalysis has also been demonstrated to be a greener and milder protocol for the thiol-ene/yne reactions in recent years. Additionally, unprecedented advancements have been achieved in this area during the past decade. In this review, we will summarize the recent advances in visible-light photoredox catalyzed thiol-ene/yne reactions from 2015 to 2021. Synthetic strategies, substrate scope, and proposed reaction pathways are mainly discussed.